Multiply -3 times the quantity (x+6)

and the equation becomes

-3x -18 +6x = 7x -10

Add -3x and 6x on the left side of the equation

3x -18 = 7x -10

The two sides of the equation are equal, so if you do the same thing to both sides they will still be equal!

Subtract 3x from both sides.

-18 = 4x -10

Add 10 to each side.

-8 = 4x

divide each side by 4

-2 = x so x = -2

Now check by substituting -2 for x in the original equation.

-3(-2+6) +6(-2) = 7(-2) - 10

Adding -2 +6

-3(4) +6(-2) = 7(-2) -10

Multiplying the terms in parenthesis

-12 -12 = -14 -10

Adding the negative terms

-24 = -24

This is true, so the answer x= -2 checks.

Always do a check when possible and correct your mistakes to get the most credit for your work.

and the equation becomes

-3x -18 +6x = 7x -10

Add -3x and 6x on the left side of the equation

3x -18 = 7x -10

The two sides of the equation are equal, so if you do the same thing to both sides they will still be equal!

Subtract 3x from both sides.

-18 = 4x -10

Add 10 to each side.

-8 = 4x

divide each side by 4

-2 = x so x = -2

Now check by substituting -2 for x in the original equation.

-3(-2+6) +6(-2) = 7(-2) - 10

Adding -2 +6

-3(4) +6(-2) = 7(-2) -10

Multiplying the terms in parenthesis

-12 -12 = -14 -10

Adding the negative terms

-24 = -24

This is true, so the answer x= -2 checks.

Always do a check when possible and correct your mistakes to get the most credit for your work.